Oxidation-resistant meta-aramid fiber and preparation method thereof
By doping meta-aramid fibers with composite reinforced nanopowders, the oxidation resistance and physical properties of carbon nanotubes are used to improve the oxidation resistance and mechanical strength of the fibers, thus solving the problem of yellowing of meta-aramid fibers during the oxidation process. problem, achieving high thermal oxygen aging resistance and improvement in mechanical strength.
Patent Information
- Application Number
- CN202411626905.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-11-14
AI Technical Summary
Meta-aramid fibers tend to turn yellow during the oxidation process, which affects their quality. At the same time, the prior art has problems of reduced performance and limited application scenarios when improving the antioxidant ability and mechanical strength.
By mixing composite nano powder in the interval theram fiber, use the antioxidant and physical properties of carbon nanoplasses to improve the oxidation ability and mechanical strength of the fiber, and unravel the common polyacheamide and inter -medium powder powder through hydrogen phosphate. Increase the decentralization and binding of carbon nanotubes in organic solvents.
It achieves high thermal and oxygen aging resistance and improved mechanical strength of meta-aramid fiber, avoiding the problems of performance degradation and limited application, while maintaining the original mechanical properties of the fiber.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of meta-aramid fibers, and in particular relates to an oxidation-resistant meta-aramid fiber and a preparation method thereof. Background Art
[0002] Meta-aramid has good thermal stability and chemical stability, high breaking strength and toughness, and excellent mechanical properties. It is often used in the military and national economic fields in the form of structural composite materials and has become an irreplaceable key material. However, the π-π bonds between the benzene rings in meta-aramid fibers are easily oxidized and turn yellow, which affects the quality of the meta-aramid fibers.
[0003] Patent CN113789583A discloses an anti-yellowing meta-aramid fiber precipitate and its preparation method and application. The method comprises gradually adding isophthaloyl chloride and a modifier containing tetramethylpiperidinamine to a solution of meta-phenylenediamine, and then adding an anti-yellowing agent, precipitating and washing to obtain a meta-aramid fiber with excellent anti-yellowing and anti-thermal oxidation properties. However, this solution introduces metal ions, which leads to a decrease in the performance of downstream products of the meta-aramid fiber and limits the application scenarios.
[0004] Patent CN117265686A discloses an oxidation-resistant meta-aramid fiber and a preparation method thereof, wherein meta-phenylenediamine and isophthaloyl chloride, diazopeptane monomers and isophthaloyl chloride are polymerized separately and then mixed, and then polymerized with isophthaloyl chloride and reacted with di-tert-butylbenzoyl chloride monomers to obtain a meta-aramid polymer solution, and then subjected to a wet spinning process to obtain an oxidation-resistant meta-aramid fiber; the fiber has good antioxidant capacity and is suitable for industrial production; however, the solution improves the antioxidant capacity of the meta-aramid polymer by changing the polymer structure of the meta-aramid, which affects the mechanical strength of the meta-aramid fiber. Summary of the invention
[0005] The purpose of the present invention is to solve the problem of how to improve the oxidation resistance and mechanical strength of meta-aramid fiber, and to provide an oxidation-resistant meta-aramid fiber and a preparation method thereof.
[0006] The purpose of the present invention can be achieved by the following technical solutions:
[0007] A method for preparing oxidation-resistant meta-aramid fiber comprises the following steps:
[0008] Step 1: The copolyamide and the meta-aramid powder are respectively modified by hydrolysis with phosphoric acid to obtain the modified copolyamide and the modified meta-aramid powder.
[0009] Step 2: Mix the carboxylated carbon nanotubes with N,N-dimethylacetamide in a reactor and perform ultrasonic treatment, add 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide to the reactor, perform ultrasonic treatment, add the modified copolyamide, perform magnetic stirring after ultrasonic treatment, then add the modified meta-aramid powder, perform magnetic stirring after ultrasonic treatment, centrifuge at 10,000 rpm, wash the precipitate with ethanol, and obtain the composite reinforced nanopowder after drying.
[0010] Step 3: Mix the composite reinforced nano powder, poly(m-phenylene isophthalamide), hydrogen chloride and N,N-dimethylacetamide to prepare a composite meta-aramid spinning solution, and use a wet spinning process to prepare oxidation-resistant meta-aramid fibers.
[0011] In step 2, the ultrasonic treatment time is 30-40 minutes, and the magnetic stirring time is 20-24 hours.
[0012] Furthermore, in step 2, the usage ratio of carboxylated carbon nanotubes, N,N-dimethylacetamide, 1-ethyl-(3-dimethylaminopropyl)carbodiimide, N-hydroxysuccinimide, modified copolyamide and modified meta-aramid powder is 5-8g: 100-150mL: 3-4mL: 5-7mL: 3-5g: 3-5g.
[0013] Furthermore, in step three, the mixing mass ratio of the composite reinforced nano powder, poly(m-phenylene isophthalamide), hydrogen chloride and N,N-dimethylacetamide is 3-4:15-20:1-4:75-85.
[0014] Further, the preparation method of carboxylated carbon nanotubes is as follows:
[0015] The carbon nanotubes and the mixed acid solution are ultrasonically mixed in a reaction kettle for 1-2 hours, heated to 70-80° C. in a water bath, stirred, condensed and refluxed for 1-1.5 hours, washed with deionized water after centrifugation, and dried to obtain carboxylated carbon nanotubes.
[0016] The mixed acid solution is prepared by mixing 98 wt % sulfuric acid and 68 wt % nitric acid in a molar ratio of 3:1.
[0017] Furthermore, the usage ratio of carbon nanotubes to mixed acid solution is 5-10 g:150-170 mL.
[0018] Furthermore, the phosphoric acid hydrolysis modification method in step 1 is:
[0019] The meta-aramid powder is mixed with 30-35 times the mass of phosphoric acid solution in a reactor, and then transferred to a high-speed disperser and mixed at a speed of 4500-5000 rpm for 5-6 minutes. After filtering, the meta-aramid powder is heated to 100-110° C. in the reactor and reacted for 30-40 minutes. The meta-aramid powder is washed with deionized water and dried to obtain modified meta-aramid powder.
[0020] Furthermore, the meta-aramid powder is prepared by freezing the meta-aramid chopped fibers in liquid nitrogen for 5-7 minutes, grinding them at 500-600 rpm for 4-5 hours in a planetary ball mill, and separating the nano-powder with a screening vibrator, and the phosphoric acid solution is a 50wt% phosphoric acid aqueous solution.
[0021] Furthermore, the phosphoric acid hydrolysis modification method of the modified copolyamide is the same as the phosphoric acid hydrolysis modification method of the meta-aramid powder.
[0022] Further, the preparation method of the copolyamide is as follows:
[0023] In a reaction kettle, p-phenylenediamine, trimesic acid and p-aminobenzoic acid are dissolved in a mixed solvent of pyridine and N,N-dimethylacetamide, and triphenyl phosphite is added after complete dissolution. The temperature is raised to 100-110°C under nitrogen protection and the reaction is carried out for 3-5 hours. Then, the mixture is slowly poured into deionized water to obtain a polymer. The polymer is washed with anhydrous ethanol, refluxed in hot water, and vacuum dried at 90-100°C for 10-12 hours to obtain a copolyamide.
[0024] Furthermore, the usage ratio of p-phenylenediamine, trimesic acid, p-aminobenzoic acid, pyridine, N,N-dimethylacetamide, and triphenyl phosphite is 10-12g:20-25g:13-15g:20-25mL:200-250mL:90-100g.
[0025] Beneficial effects of the present invention:
[0026] (1) The oxidation-resistant meta-aramid fiber prepared by the present invention is prepared by doping the meta-aramid fiber with a composite reinforcing nanopowder, so that the composite reinforcing nanopowder modified by carbon nanotubes enhances the performance of the oxidation-resistant meta-aramid fiber, and the oxidation resistance of the oxidation-resistant meta-aramid fiber is improved by utilizing the antioxidant property of the carbon nanotubes. At the same time, the physical properties of the carbon nanotubes themselves also enhance the mechanical strength of the oxidation-resistant meta-aramid fiber, and the obtained oxidation-resistant meta-aramid fiber has good resistance to heat and oxygen aging.
[0027] (2) The preparation method of the present invention prepares an easily soluble copolyamide and modifies it with phosphoric acid, and then uses the copolyamide to graft the copolyamide onto the carboxylated carbon nanotubes by amide dehydration condensation reaction to improve the dispersibility of the carboxylated carbon nanotubes in organic solvents. The remaining carboxyl groups on the copolyamide are then used to carry out amide dehydration condensation with the meta-aramid powder modified with phosphoric acid, and the carbon nanotubes are composited with the meta-aramid powder by using the copolyamide to improve the dispersibility of the carbon nanotubes in the composite meta-aramid spinning solution, thereby utilizing the highly dispersed carbon nanotubes to improve the oxidation resistance and mechanical strength of the meta-aramid fiber.
[0028] (3) The preparation method of the present invention does not change the principle of wet spinning of meta-aramid fiber. The method is simple and easy to obtain, and there is no need to change the equipment and parameters of the wet spinning process. It only needs to prefabricate composite reinforced nanopowder and then use the composite reinforced nanopowder as a raw material for the wet spinning process and mix it with the meta-aramid spinning solution to obtain oxidation-resistant meta-aramid fiber, which has strong market application capabilities. DETAILED DESCRIPTION
[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Embodiment 1: A method for preparing oxidation-resistant meta-aramid fiber, comprising the following steps:
[0031] Step 1: Dissolve 10 g of p-phenylenediamine, 20 g of trimesic acid and 13 g of p-aminobenzoic acid in a mixed solvent of 20 mL of pyridine and 200 mL of N,N-dimethylacetamide in a reactor. After complete dissolution, add 90 g of triphenyl phosphite and heat to 100 ° C under nitrogen protection to react for 3 hours. Then slowly pour into deionized water to obtain a polymer. Wash the polymer with anhydrous ethanol, reflux in hot water, and vacuum dry at 90 ° C for 10 hours to obtain a copolyamide.
[0032] Step 2: Mix 8 g of copolyamide with 240 g of 50 wt% phosphoric acid solution in a reactor, transfer to a high-speed disperser and mix at 4500 rpm for 5 min, filter and heat the copolyamide in the reactor to 100 ° C and react for 30 min, wash the copolyamide with deionized water until the last washing liquid is neutral, and then vacuum dry at 90 ° C for 8 h to obtain a modified copolyamide.
[0033] Step 3: Mix 8 g of meta-aramid powder with 240 g of 50 wt% phosphoric acid solution in a reactor, transfer to a high-speed disperser and mix at 4500 rpm for 5 min. After filtering, heat the meta-aramid powder to 100 ° C in the reactor and react for 30 min. Wash the meta-aramid powder with deionized water until the last washing liquid is neutral, and then vacuum dry at 90 ° C for 8 h to obtain modified meta-aramid powder.
[0034] The meta-aramid powder is prepared by freezing the meta-aramid chopped fibers in liquid nitrogen for 5 minutes, grinding them at 500 rpm for 4 hours in a planetary ball mill, and separating the nano-powder with a screening vibrator to obtain the meta-aramid powder.
[0035] Step 4: Take 5g of carbon nanotubes and 150mL of mixed acid solution and mix them ultrasonically in a reactor for 1h. The mixed acid solution is prepared by mixing 98wt% sulfuric acid and 68wt% nitric acid in a molar ratio of 3:1. Heat to 70°C in a water bath, stir, condense and reflux for 1h, wash the precipitate with deionized water after centrifugation until the last washing liquid is neutral, and dry at 70°C for 10h to obtain carboxylated carbon nanotubes.
[0036] Step 5. Ultrasonic mix 5 g of carboxylated carbon nanotubes with 100 mL of N,N-dimethylacetamide in a reactor for 30 min, add 3 mL of 1-ethyl-(3-dimethylaminopropyl)carbodiimide and 5 mL of N-hydroxysuccinimide to the reactor, ultrasonically treat for 30 min, then add 3 g of modified copolyamide, magnetically stir for 20 h, and then add 3 g of modified meta-aramid powder, ultrasonically treat for 30 min, then magnetically stir for 20 h, centrifuge at 10000 rpm, wash the precipitate with ethanol, and dry at 50 ° C for 1 h to obtain a composite reinforced nanopowder.
[0037] Step 6: 30 g of composite reinforced nano powder, 150 g of poly(m-phenylene isophthalamide), 10 g of hydrogen chloride and 750 g of N,N-dimethylacetamide are mixed to prepare a composite meta-aramid spinning solution, and oxidation-resistant meta-aramid fiber is prepared by wet spinning process.
[0038] Embodiment 2: A method for preparing oxidation-resistant meta-aramid fiber, comprising the following steps:
[0039] Step 1: Dissolve 11 g of p-phenylenediamine, 22.5 g of trimesic acid and 14 g of p-aminobenzoic acid in a mixed solvent of 22.5 mL of pyridine and 225 mL of N,N-dimethylacetamide in a reactor. After complete dissolution, add 95 g of triphenyl phosphite and heat to 105 ° C under nitrogen protection for 4 hours. Then slowly pour into deionized water to obtain a polymer. Wash the polymer with anhydrous ethanol, reflux in hot water, and vacuum dry at 95 ° C for 11 hours to obtain a copolyamide.
[0040] Step 2: Mix 9 g of copolyamide with 300 g of 50 wt% phosphoric acid solution in a reactor, transfer to a high-speed disperser and mix at 4700 rpm for 5.5 min. After filtering, heat the copolyamide to 105° C. in the reactor and react for 35 min. Wash the copolyamide with deionized water until the last washing liquid is neutral, and then vacuum dry at 95° C. for 9 h to obtain a modified copolyamide.
[0041] Step 3: Mix 9 g of meta-aramid powder with 300 g of 50 wt% phosphoric acid solution in a reactor, transfer to a high-speed disperser and mix at 4700 rpm for 5.5 min. After filtering, heat the meta-aramid powder to 105 ° C in the reactor and react for 35 min. Wash the meta-aramid powder with deionized water until the last washing liquid is neutral, and then vacuum dry at 95 ° C for 9 h to obtain modified meta-aramid powder.
[0042] The meta-aramid powder is prepared by freezing the meta-aramid chopped fibers in liquid nitrogen for 6 minutes, grinding them at 550 rpm for 4.5 hours in a planetary ball mill, and separating the nano-powder with a screening vibrator to obtain the meta-aramid powder.
[0043] Step 4: Take 7.5g of carbon nanotubes and 160mL of mixed acid solution and mix them ultrasonically in a reactor for 1.5h. The mixed acid solution is prepared by mixing 98wt% sulfuric acid and 68wt% nitric acid in a molar ratio of 3:1. Heat to 75°C in a water bath, stir, condense and reflux for 1.25h, wash the precipitate with deionized water after centrifugation until the last washing liquid is neutral, and dry at 75°C for 11h to obtain carboxylated carbon nanotubes.
[0044] Step 5. In a reactor, 6.5 g of carboxylated carbon nanotubes were ultrasonically mixed with 125 mL of N, N-dimethylacetamide for 35 min, 3.5 mL of 1-ethyl-(3-dimethylaminopropyl)carbodiimide and 6 mL of N-hydroxysuccinimide were added to the reactor, and ultrasonic treatment was performed for 35 min. Then, 4 g of modified copolyamide was added, and magnetic stirring was performed for 22 h. Then, 4 g of modified meta-aramid powder was added, and the mixture was ultrasonically treated for 35 min and magnetically stirred for 22 h. After centrifugation at 10,000 rpm, the precipitate was washed with ethanol, and dried at 55 ° C for 1.5 h to obtain a composite reinforced nanopowder.
[0045] Step 6: 35 g of composite reinforced nano powder, 175 g of poly(m-phenylene isophthalamide), 25 g of hydrogen chloride and 800 g of N,N-dimethylacetamide are mixed to prepare a composite meta-aramid spinning solution, and oxidation-resistant meta-aramid fiber is prepared by wet spinning process.
[0046] Embodiment 3: A method for preparing oxidation-resistant meta-aramid fiber, comprising the following steps:
[0047] Step 1: Dissolve 12 g of p-phenylenediamine, 25 g of trimesic acid and 15 g of p-aminobenzoic acid in a mixed solvent of 25 mL of pyridine and 250 mL of N,N-dimethylacetamide in a reactor. After complete dissolution, add 100 g of triphenyl phosphite and heat to 110 ° C under nitrogen protection for reaction for 5 hours. Then slowly pour into deionized water to obtain a polymer. Wash the polymer with anhydrous ethanol, reflux in hot water, and vacuum dry at 100 ° C for 12 hours to obtain a copolyamide.
[0048] The copolyamide has good solubility and dispersibility in organic solvents and contains amide groups, which are convenient for grafting reaction with other groups and are beneficial for the substances grafted with the copolyamide to be dispersed in the organic solvent of the meta-aramid fiber.
[0049] Step 2: Mix 10 g of the copolyamide with 350 g of a 50 wt% phosphoric acid solution in a reactor, transfer the mixture to a high-speed disperser and mix at 5000 rpm for 6 min. After filtering, heat the copolyamide to 110° C. in the reactor and react for 40 min. Wash the copolyamide with deionized water until the last washing liquid is neutral, and then vacuum dry it at 100° C. for 10 h to obtain a modified copolyamide.
[0050] Step 3: Mix 10 g of meta-aramid powder with 350 g of 50 wt% phosphoric acid solution in a reactor, transfer to a high-speed disperser and mix at 5000 rpm for 6 min, filter and heat the meta-aramid powder to 110 ° C in the reactor for 40 min, wash the meta-aramid powder with deionized water until the last washing liquid is neutral, and then vacuum dry at 100 ° C for 10 h to obtain modified meta-aramid powder.
[0051] The meta-aramid powder is prepared by freezing the meta-aramid chopped fibers in liquid nitrogen for 7 minutes, grinding them at 600 rpm for 5 hours in a planetary ball mill, and separating the nano-powder with a screening vibrator to obtain the meta-aramid powder.
[0052] The oxidizing property of phosphoric acid itself is utilized to oxidize and hydrolyze part of the amide bonds in the surface structure of the copolyamide and meta-aramid powder to form amino and carboxyl groups, thereby improving the reaction grafting ability of the surface of the modified copolyamide and modified meta-aramid powder. The phosphoric acid remaining on the surface of the copolyamide and modified meta-aramid will be dehydrated and polymerized into diphosphoric acid at a temperature of 100-110°C. The diphosphoric acid reacts with the amide bonds in the copolyamide structure, thereby improving the activity of the modified copolyamide and modified meta-aramid surface, and improving the interfacial bonding performance of the modified copolyamide and carbon nanotubes in the subsequent reaction.
[0053] Step 4: Take 10g of carbon nanotubes and 170mL of mixed acid solution and mix them ultrasonically in a reactor for 2h. The mixed acid solution is prepared by mixing 98wt% sulfuric acid and 68wt% nitric acid in a molar ratio of 3:1. Heat to 80°C in a water bath, stir, condense and reflux for 1.5h, wash the precipitate with deionized water after centrifugation until the last washing liquid is neutral, and dry at 80°C for 12h to obtain carboxylated carbon nanotubes.
[0054] Step 5. In a reactor, 8 g of carboxylated carbon nanotubes were ultrasonically mixed with 150 mL of N, N-dimethylacetamide for 40 min, 4 mL of 1-ethyl-(3-dimethylaminopropyl)carbodiimide and 7 mL of N-hydroxysuccinimide were added to the reactor, and ultrasonic treatment was performed for 40 min. Then, 5 g of modified copolyamide was added, and magnetic stirring was performed for 24 h. Then, 5 g of modified meta-aramid powder was added, and the mixture was ultrasonically treated for 40 min and magnetically stirred for 24 h. After centrifugation at 10,000 rpm, the precipitate was washed with ethanol, and dried at 60 ° C for 2 h to obtain a composite reinforced nanopowder.
[0055] Step 6: 40 g of composite reinforced nano powder, 200 g of poly(m-phenylene isophthalamide), 40 g of hydrogen chloride and 850 g of N,N-dimethylacetamide are mixed to prepare a composite meta-aramid spinning solution, and oxidation-resistant meta-aramid fiber is prepared by wet spinning process.
[0056] After the carboxylated carbon nanotubes are ultrasonically dispersed in N,N-dimethylacetamide, the carboxyl groups of the carboxylated carbon nanotubes are converted into semi-stable reactive amine esters under the action of 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide, and then react with the amino groups on the added modified copolyamide to form stable amide bonds, and the modified copolyamide is grafted on the surface of the carboxylated carbon nanotubes. The good solubility of the modified copolyamide in N,N-dimethylacetamide is utilized to improve the dispersibility of the carboxylated carbon nanotubes in N,N-dimethylacetamide, reduce the agglomeration of the carboxylated carbon nanotubes and reduce the coagulation phenomenon; then, phosphoric acid-modified meta-aramid powder is added to make the carboxyl groups on the surface of the modified meta-aramid powder react with The remaining amino groups on the modified copolyamide react to form stable amide bonds, so that the carbon nanotubes are attached to the surface of the modified meta-aramid powder under the bonding effect of the modified copolyamide and the bonding ability of the modified copolyamide surface. The modified meta-aramid powder is mixed with the meta-aramid spinning solution. Since the modified meta-aramid powder will not dissolve in organic solvents, the modified meta-aramid powder is used as a carrier to fuse the modified meta-aramid powder into the meta-aramid fiber, thereby compounding the carbon nanotubes with the meta-aramid fiber, replacing part of the benzene rings with the carbon nanotubes to form π-π bonds with the meta-aramid, reducing the easily oxidized bonds between the benzene rings, and improving the oxidation resistance of the meta-aramid fiber.
[0057] Comparative Example 1: The difference from Example 1 is that in step five, no modified copolyamide is added.
[0058] Comparative Example 2: The difference from Example 1 is that in step five, no modified meta-aramid powder is added.
[0059] Comparative Example 3: The difference from Example 1 is that no composite reinforcing nano powder is added in step six.
[0060] The sources of some reagents in the embodiments and comparative examples are as follows:
[0061] The carbon nanotubes are multi-walled carbon nanotubes with a diameter of 10-15 nm and a length of less than 100 μm, and are commercially available.
[0062] p-Phenylenediamine, trimesic acid, p-aminobenzoic acid and triphenyl phosphite were purchased from Sinopharm Chemical Reagent Co., Ltd.
[0063] Meta-aramid chopped fibers, length 3-12mm, density 1.38g / cm 3 , purchased from Zhongfang Special Fiber Co., Ltd.
[0064] N,N-dimethylacetamide, pyridine, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide were all purchased from Sigma-Aldrich.
[0065] The performance tests were conducted on the samples obtained in Examples 1 to 3 and Comparative Examples 1 to 3. The meta-aramid fibers of the same size obtained by conventional wet spinning process in each Example and Comparative Example were cut into fiber bundles with a length of 100 mm, added into a sealed container containing 40 mL of methanol, and ultrasonically treated at 60° C. for 1 h. The solution was filtered using a 0.45 μm filter head, and the samples to be tested were obtained after drying. 1 g of the fiber bundles were taken for performance tests. The test method was as follows: at a temperature of 20° C. and a relative humidity of 65%, the humidity was adjusted for 16 h, and the breaking strength and breaking elongation of the fiber were tested using an electronic single fiber strength tester according to GB / T 14337-2008, with a clamping distance of 20 mm and a stretching speed of 20 mm / min.
[0066] After the fiber bundle was subjected to thermal oxidative aging treatment, the performance test was performed again. The method of thermal oxidative aging treatment is: the fiber bundle is wound and placed in a crucible, and the crucible is placed in a high-temperature oven. The treatment temperature is 300°C and the treatment time is 500 hours. After the fiber bundle is cooled, the fiber bundle is taken out to test the breaking strength and breaking elongation. The breaking strength retention rate and breaking elongation retention rate of the fiber bundle compared with the fiber bundle not subjected to thermal oxidative aging treatment are calculated. The results are shown in Table 1:
[0067] Table 1
[0068] project Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Breaking strength cN / dtex 6.08 6.10 6.11 5.56 5.92 5.54 Elongation at break % 35.5 35.6 35.8 32.1 33.2 32.9 Retention rate of breaking strength % 68.4 68.5 68.8 56.3 63.7 58.6 Retention rate of elongation at break % 56.9 57.2 57.3 41.5 52.6 42.4
[0069] It can be seen from Table 1 that the oxidation-resistant meta-aramid fiber prepared by the present invention has significantly improved breaking strength and breaking elongation compared with the blank comparative example 3, and the breaking strength retention rate and breaking elongation retention rate after 500h thermal oxidation aging are relatively high, indicating that the oxidation-resistant meta-aramid fiber prepared by the present invention has good antioxidant ability; since comparative example 1 does not add modified copolyamide, the carboxylated carbon nanotubes have insufficient dispersibility in N,N-dimethylacetamide, poor bonding with modified meta-aramid, low dispersion in the composite meta-aramid spinning solution, and agglomeration occurs, so the obtained oxidation-resistant meta-aramid fiber has poor mechanical properties and low oxidation resistance; since comparative example 2 does not add modified meta-aramid powder, when the composite meta-aramid spinning solution is prepared, the bonding strength with the oxidation-resistant meta-aramid fiber spun by wet method is low, and it is easy to fall off, so the performance is low and the oxidation resistance is insufficient.
[0070] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0071] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing oxidation-resistant meta-aramid fiber, characterized in that: The steps include: Step 1: hydrolyzing the copolyamide and the meta-aramid powder with phosphoric acid to obtain a modified copolyamide and a modified meta-aramid powder; Step 2: Mix the carboxylated carbon nanotubes with N,N-dimethylacetamide in a reactor and perform ultrasonic treatment, add 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide to the reactor, perform ultrasonic treatment, add the modified copolyamide, perform magnetic stirring after ultrasonic treatment, then add the modified meta-aramid powder, perform magnetic stirring after ultrasonic treatment, centrifuge at a speed of 10000 rpm, wash the precipitate with ethanol, and obtain the composite reinforced nano powder after drying; Step 3: Mixing composite reinforced nano powder, poly(m-phenylene isophthalamide), hydrogen chloride and N,N-dimethylacetamide to prepare composite meta-aramid spinning solution, and preparing oxidation-resistant meta-aramid fiber by wet spinning process; The ultrasonic treatment time in step 2 is 30-40 minutes, and the magnetic stirring time is 20-24 hours.
2. The method for preparing an oxidation-resistant meta-aramid fiber according to claim 1, characterized in that: The amount ratio of the carboxylated carbon nanotubes, N,N-dimethylacetamide, 1-ethyl-(3-dimethylaminopropyl)carbodiimide, N-hydroxysuccinimide, modified copolyamide and modified meta-aramid powder in step 2 is 5-8g: 100-150mL: 3-4mL: 5-7mL: 3-5g: 3-5g.
3. The method for preparing an oxidation-resistant meta-aramid fiber according to claim 1, characterized in that: The mixing mass ratio of the composite reinforced nano powder, poly(m-phenylene isophthalamide), hydrogen chloride and N,N-dimethylacetamide in step three is 3-4:15-20:1-4:75-85.
4. The method for preparing an oxidation-resistant meta-aramid fiber according to claim 1, characterized in that: The preparation method of the carboxylated carbon nanotubes is as follows: The carbon nanotubes and the mixed acid solution are ultrasonically mixed in a reaction kettle for 1-2 hours, heated in a water bath to 70-80° C., stirred, condensed and refluxed for 1-1.5 hours, washed with deionized water after centrifugation, and dried to obtain carboxylated carbon nanotubes; The mixed acid solution is prepared by mixing 98 wt % sulfuric acid and 68 wt % nitric acid in a molar ratio of 3:
1.
5. The method for preparing oxidation-resistant meta-aramid fiber according to claim 4, characterized in that: The usage ratio of the carbon nanotubes to the mixed acid solution is 5-10 g:150-170 mL.
6. The method for preparing oxidation-resistant meta-aramid fiber according to claim 1, characterized in that: The method of phosphoric acid hydrolysis modification in step 1 is: The meta-aramid powder is mixed with 30-35 times the mass of phosphoric acid solution in a reactor, and then transferred to a high-speed disperser and mixed at a speed of 4500-5000 rpm for 5-6 minutes. After filtering, the meta-aramid powder is heated to 100-110° C. in the reactor and reacted for 30-40 minutes. The meta-aramid powder is washed with deionized water and dried to obtain modified meta-aramid powder.
7. The method for preparing oxidation-resistant meta-aramid fiber according to claim 6, characterized in that: The meta-aramid powder is prepared by freezing the meta-aramid chopped fibers in liquid nitrogen for 5-7 minutes, grinding them for 4-5 hours at 500-600 rpm in a planetary ball mill, and separating the nano-powder with a screening vibration machine. The phosphoric acid solution is a 50wt% phosphoric acid aqueous solution.
8. The method for preparing oxidation-resistant meta-aramid fiber according to claim 1, characterized in that: The preparation method of the copolyamide is as follows: In a reaction kettle, p-phenylenediamine, trimesic acid and p-aminobenzoic acid are dissolved in a mixed solvent of pyridine and N,N-dimethylacetamide, and triphenyl phosphite is added after complete dissolution. The temperature is raised to 100-110°C under nitrogen protection and the reaction is carried out for 3-5 hours. Then, the mixture is slowly poured into deionized water to obtain a polymer. The polymer is washed with anhydrous ethanol, refluxed in hot water, and vacuum dried to obtain a copolyamide.
9. The method for preparing oxidation-resistant meta-aramid fiber according to claim 8, characterized in that: The dosage ratio of p-phenylenediamine, trimesic acid, p-aminobenzoic acid, pyridine, N,N-dimethylacetamide and triphenyl phosphite is 10-12g: 20-25g: 13-15g: 20-25mL: 200-250mL: 90-100g.
10. An oxidation-resistant meta-aramid fiber, characterized in that: Prepared by the preparation method described in any one of claims 1 to 9.
Citation Information
Patent Citations
Anti-yellowing meta-aramid precipitation fiber as well as preparation method and application thereof
CN113789583A
Oxidation-resistant meta-aramid fiber and preparation method thereof
CN117265686A
Method for preparing conduction meta-position aramid fibers
CN103046155A
Polyethyleneimine functionalized carbon nanotube modified polyformaldehyde composite material and preparation method thereof
CN110527243A
Preparation method of tensile carbon nanotube modified aramid fiber
CN116716721A
Cited By
Modified meta-aramid composite fiber and preparation method thereof
CN120443371A